On Some Fiscal Decisions of Caligula and Vespasian - Pikulska-Radomska, Anna (Studia Ceranea, 2012)
The history of the Roman Empire is a history of continuously looking for new sources of state revenues. Numerous public loads, spontaneously created during the early Empire, without any deeper analysis, created a disordered mess of particular and curious taxes rather than a centralized system as an instrument of controlling economic processes. The tax decisions of the emperors mentioned in the title, in spite of having a significant influence on the state treasury, were, in fact, of the same disordered nature.